2023
DOI: 10.12911/22998993/162775
|View full text |Cite
|
Sign up to set email alerts
|

Potato with Colored Flesh Valuable and Attractive to the Consumer

Abstract: The purpose of this paper was to determine the vitamin C content and the selected consumption features (tastiness and cooking type) in edible potato tubers with colored flesh. The research material consisted of tubers of eight edible potato cultivars collected from a field experiment conducted in 2021 and 2022 at the Agricultural Experimental Station in Zawady of Siedlce University of Natural Sciences and Humanities (52 o 03'N; 22 o 33'E). The following cultivars were grown: two cultivars with red flesh -Rote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Coloured potato crisps and other snacks prepared from red and purple esh potato cultivars are an innovative alternative to conventional potato crisps due to their higher content of phenolic compounds which might make them healthier compared to conventional crisps 26, [29][30] . Purple esh potatoes are an option which adds colour to the menu, and enrich human diet in additional nutritional components 4,31 . The purpose of the study reported here was to compare contents of basic components, that is starch and dry matter, of table potato tubers to coloured esh cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Coloured potato crisps and other snacks prepared from red and purple esh potato cultivars are an innovative alternative to conventional potato crisps due to their higher content of phenolic compounds which might make them healthier compared to conventional crisps 26, [29][30] . Purple esh potatoes are an option which adds colour to the menu, and enrich human diet in additional nutritional components 4,31 . The purpose of the study reported here was to compare contents of basic components, that is starch and dry matter, of table potato tubers to coloured esh cultivars.…”
Section: Introductionmentioning
confidence: 99%